A BIBLIOGRAPHIC SURVEY OF HISTORICAL ARTICLES IN THE ETHIOPIAN HERALD (1943-1963)1 - Abebe Dires (European Scientific Journal, ESJ, 2012)
The period that followed the end of the Second World War was important for Ethiopia. There were many sweeping changes in the political life of the country. After the return of the Emperor Haile Selasssie I to Ethiopia from exile (England), there were many changes introduced in an effort to strengthen the central government and modernization. However, much of what has been said in many of the government media was more with propaganda theme than reality. And this was one of the political plays of the time as far as the Imperial Throne was concerned. The objective of this article is to see the contents and give analysis of selected articles in the Ethiopian Herald with political and historical themes with propaganda orientations from 1943-1963.